Case report of disseminated borrelial lymphocytoma with isolation of Borrelia burgdorferi sensu stricto in chronic lymphatic leukemia stage Binet A—an 11 year follow up - Hofmann, Heidelore; Margos, Gabriele; Todorova, Antonia; Ringshausen, Ingo; Kuleshov, Konstantin; Fingerle, Volker (Frontiers in Medicine, 2024)
We report a rare manifestation of cutaneous borreliosis in a patient with pre-existing malignant lymphoproliferative disease, in particular chronic lymphocytic B cell leukemia (B-CLL). The patient’s cutaneous lesions were initially diagnosed histologically as leukemia cutis. Distribution pattern of the skin lesions were in typical localizations for borrelial lymphocytoma. Borrelia burgdorferi sensu stricto was isolated and cultured from two sites (ear, mammilla). Antibiotic therapy improved the cutaneous lesions and the general condition of the patient. However, a second round of antibiotic therapy was required to resolve the lesions. At eleven years of follow-up the patient’s skin was clear and she still had a stable condition of B-CLL without chemotherapy. In conclusion, the patient suffered from Lyme borreliosis (Borrelia lymphocytoma) and the cutaneous symptoms were aggravated by the underlying condition of chronic B-CLL condition.